Calibration of triaxial MEMS vector field measurement system. Issue 6 (1st November 2014) - Xiaoming, Zhang; Guobin, Chen; Jie, Li; Jun, Liu
Abstract : Triaxial MEMS vector field measurement system with triaxial MEMS sensors, such as accelerometer and magnetometer, is typically used to acquire navigation information in strap‐down inertial navigation system (SINS). The navigation accuracy of the body is directly affected by the measurement accuracy of the measurement system. This study presents a two‐step calibration algorithm for the triaxial MEMS vector field measurement system based on a detailed analysis of the measurement system error model. In the calibration procedure of this method, the first step is to calibrate the triaxial vector sensor error, including bias, scale factors and non‐orthogonality using the ellipsoid fitting method; the second step is to calibrate the misalignment between the orthogonal sensor frame and the system body frame using the four‐position method. Furthermore, the mathematical analysis of four‐position method calibration error is done to study on the factors influencing the misalignment calibration accuracy, numerical simulation and experiments, which are performed for validating the analysis. A series of calibration experiments on a triaxial MEMS accelerometer in the measurement system show signiﬁcant enhancement of the accuracy of three components measurement data in the system body frame.